2006
DOI: 10.17348/era.4.0.11-24
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization and Conservation of Himalayan Medicinal Plants: <i>Angelica glauca</i> Edgew. as a case study

Abstract: Research AbstractThe present study broadly supports the need for conservation initiatives for Himalayan medicinal plants. An approach is set up for prioritization grading of the importance of medicinal plants that is based upon the knowledge of local communities about the species. The study of Himalayan medicinal plants in general and Angelica glauca Edgew. in particular reveals that the utilization pattern, traditional knowledge base and trade of medicinal plants show trends that are not ideal for sustainabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 7 publications
(5 reference statements)
4
12
0
1
Order By: Relevance
“…A similar observation was reported on Himalayan medicinal plants (India) (Bisht et al 2006). In contrast, Gidey et al (2009) reported a positive and significant correlation between gender and the number of species reported among the Bench ethnic group.…”
Section: Knowledge Distribution Of Medicinal Plantssupporting
confidence: 83%
“…A similar observation was reported on Himalayan medicinal plants (India) (Bisht et al 2006). In contrast, Gidey et al (2009) reported a positive and significant correlation between gender and the number of species reported among the Bench ethnic group.…”
Section: Knowledge Distribution Of Medicinal Plantssupporting
confidence: 83%
“…These four tree species which need to be given high preference in terms of conservation are: Berchemia discolor, Hyphaene petersiana , Sclerocarya birrea and Diospyros mespiliformis . This high preference rank is known to be an important index in identifying plants of potentially high conservation concern [24,38]. These species have been utilized differently in Namibia of which Sclerocarya birrea has received more attention in term of domestication and cultivars for fruit production and because of its by-products verities.…”
Section: Resultsmentioning
confidence: 99%
“…They depend upon the bio-resources for their primary health care because they perceive that the traditional medicines have no or lesser side affects (Kamboj 2000). Although studies of medicinal plant use by Himalaya tribes have been conducted (e.g., Bisht et al 2006, Hussain & Khaliq 1996, few ethnobotanical studies of medicinal plants of Gilgit district and its surrounding areas have been completed (e.g., Kazmi & Siddiqui 1953). In view of this, the present study was conducted to identifying the medicinal plants of this district and their utilization for primary health care treatments of common ailments.…”
Section: Ethnobotanical Studies Of Medicinal Plants Of Gilgit Districmentioning
confidence: 99%